Letter (copy) : International Brigade - Citrine, Walter, 1887-1983
034-0155-001 Secretary's . WMC/FC/EK/1718. 26th August, 1938. Mr. G. Morris, South Wales Regional Council of Labour, Transport House, 42, Charles Street, CARDIFF. Dear Mr. Morris, INTERNATIONAL BRIGADE. Referring to your letter of the 23rd instant, no money from the International Solidarity Fund has been allocated to the Fund for the assistance of the International Brigade Wounded and Dependents Fund. The monies raised by the International Solidarity Fund have been clearly stipulated as being for the assistance of the workers of Spain, and whilst consideration has been given to the possibility of making a grant to the fund you mention, it was felt that in view of the specific nature of our appeal this request could not be acceded to. Yours sincerely, General Secretary. 292/946/34/155